Hubungan Intensitas Bermain Game Online PUBG Mobile dan Konformitas Teman Sebaya Dengan Perilaku Agresif pada Remaja - Bagoes Praswanda, Yusrizal; Pudjo Santosa, Hedi; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the relationship between the intensity of playing PUBG Mobile online games and peer conformity with aggressive behaviour in adolescents. PUBG Mobile (Player Unknown's Battleground) is currently one of the most popular online games played by teenagers. According to data, as many as 555 million people worldwide downloaded PUBG mobile online game and Indonesia itself ranks as the second most active PUBG mobile player every month with 100 million active players every month. The number of players with the intensity of playing PUBG players will cause these players to behave aggressively. Aggressive behaviour itself occurs due to several factors, one of which is peer conformity. Teenagers will imitate the behaviour of their group friends with the aim of being accepted in the group. If the group friends behave aggressively, the teenager will imitate and also behave aggressively. The theory used in this study is the General Aggression Model (GAM) Theory and Social Learning Theory. To determine the sample, this study uses a non-probability sampling technique. The number of samples studied amounted to 100 respondents with active characteristics of playing PUBG mobile online games with ages 18-22 years. Tests in this study used the Pearson Product Moment Correlation Test. The results of this study indicate that the relationship between the intensity of playing PUBG mobile online games with aggressive behaviour has a significance value of 0.000 which means it is very significant with a correlation coefficient value of 0.342. Then, the relationship between peer conformity and aggressive behaviour in adolescents has a significance value of 0.000. which means it is significant with a correlation coefficient value of 0.481.